Development of Multimedia Power Point to Foster Students' Interest in Learning in Solar System Science Subjects in Elementary Schools - Nur Anisa (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
In an increasingly growing era like today, technology offers many ways for teachers to get around students' low interest in learning in the classroom. Low student interest often occurs due to feelings of boredom and boredom of learning, which is one of the reasons because the learning media offered by teachers is less attractive to students. The purpose of this research is to see how the procedure for developing multimedia-based power points in order to foster students' interest in learning in elementary schools. The type of research used is a qualitative approach with case study methods and data collection techniques through interviews, observations, and documentation. The development of multimedia-based power points is carried out with the ADDIE model which consists of 5 stages, namely; analysis, design, development, implementation, and evaluation. Aspects that can be grown through the development of multimedia-based power points include learning motivation and students' enthusiasm for learning.